Detection of change: Role of stimulus type versus stimulus complexity - Norvilas, Algis; Mackey, Teresa (Psichologija, 2005)
This study has investigated the claim that detection of change for spatial configuration is inherently easier than for object identity. Specifically, it looked at whether a difference in complexity, which was much greater in object than in configuration stimuli, might have mediated the difference in performance. In order to assess this possibility, participants were asked to detect change both for object and configuration stimulus pairs at two levels of complexity: simple and complex. The results showed that participants were much better at detecting change for simple stimuli than for complex stimuli, regardless of the type of stimulus involved. These findings, then, do not support a special status for configuration, rather they point to stimulus complexity as playing a determinate role in change detection.